Some observations on the moulting of black tiger shrimp, Penaeus monodon (Fab.) in controlled aquatic environment - MOHANTY, RAJEEB K (The Indian Journal of Animal Sciences, 2014)
The present study was carried out at ’shrimp culture pilot project’, Chandipur coast of Orissa, India, during 1997-1998, to study the moulting interval, moulting behaviour and weight loss after moulting of black tiger shrimp Penaeus monodon, in semi-intensive culture system. Significant relationship was established between the size of shrimp and moult cycle duration. Juveniles moulted faster with short moult cycle, while in adults it was just reverse. The moult cycle duration and moulting interval increases as size of shrimp increases. The average moulting interval for 1-2 g, 3-5 g, 6-9 g, 10-15 g, 1621 g and 22-40 g size group was 177Â± 16 hr, 216Â± 12 hr, 252Â± 16 hr, 276Â± 11 hr, 300Â± 14 hr and 326Â± 18 hr’ respectively. Females of same size group moulted significantly faster than males. It was total alkalinity of pond water (108-119 ppm) that had a definite relation with moulting process than other hydrological parameters, which showed a specific narrow range variation during the time of moulting at different growth stage. The average percentage loss in weight of P.monodon after moulting was 10.76% ofthe total body weight, probably because of loss of appetite, nutritional loss and removal of old exoskeleton.